ANALISIS PENGENDALIAN KUALITAS PADA PT. SEMARANG MAKMUR SEMARANG - Prestianto, Bayu; Sugiono, Sugiono; R, Susilo Toto (JURNAL BISNIS STRATEGI, 2003)
Quality is one of the problem which is often incorrect to be understood. Quality is illustrated as symbol of beauty, goodness, expensiveness and luxury. Those all make quality becoming difficult thing to be understood and handled. Perhaps, quality is the best manner to determine the customer's loyalty. Quality is also as defence tool from the competitor attack and as away to place in solid development and profit. The purpose of this thesis are: the first, to analyze the influence of line manufacturing (line I and II) of the thickness and the length of GIS at the department of production PT.Semarang Makmur; the second, to analyze the influence of production time of thicness and the length of GIS at the department of production PT.Semarang Makmur; the third, to analyze the process capability of production PT.Semarang Makmur with anlyzing tools such as SPC Variable and Atribut. And the fourth, to anlyze the variance of the thickness and the length those are to anlyze the degree of product damage of GIS with cause and effect diagram. With the above steps, the line influence of production the thickness and the length of GIS are not found, there is shift influence of the thickness and the length of GIS at both lines of production, there is time influence of production the thickness and the length of GIS. Then with SPC Variable and attribute is found that the production process in line I and II in producing GIS based on the thickness is capable but the process of product is being produced that is accordance with spesification; the production process in line I and II in producing GIS based on the length is not capable and the process at the product is being produced that Is not accordance wffh spesification. From the problem investigation with caused and effect diagram, the problem are found that may cause output variation. The mentioned problem is devided into five main part those are: the first, the work method that consist of tum over shift, evening shift, the error of SOP; the second, the machinery consist of machine maintanance, machine damage, setting error; the third, the work environment consist of voice pollution, room temperature, lighting, air polution; the fourth, the raw material consists of supplier, material handling, the raw material go down; the fifth, the employee consist of solidarity, less dicipline, skill and tiredness. From the problem investigation with cause and effect diagram above and the tree diagram can be achieved the solution that is found in the managerial implication.